2011
DOI: 10.1007/s00464-011-1979-4
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Nissen fundoplication with or without short gastric vessel division: a meta-analysis

Abstract: Based on this review, SGVD in LNF is associated with longer operative time and hospital stay. However, there is no difference in terms of functional outcomes for 1- and 10-year follow-up. Routine use of SGVD may therefore not be necessary in LNF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 33 publications
0
6
0
2
Order By: Relevance
“…The most hotly debated modification is the dissection of short gastric vessels, and there is no consensus on whether it is needed [18][19][20]. It is known that tying these vessels causes symptoms such as bloating, not being able to belch, and excessive flatulence instead of recurring reflux symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The most hotly debated modification is the dissection of short gastric vessels, and there is no consensus on whether it is needed [18][19][20]. It is known that tying these vessels causes symptoms such as bloating, not being able to belch, and excessive flatulence instead of recurring reflux symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…There were no perioperative deaths. In a similar systematic review, a meta-analysis of five randomised trials with 388 nontransplant patients with GOR found that perioperative morbidity occurred in 14% of patients and dysphagia developed in 17% of patients [140]. There were no perioperative deaths.…”
Section: Remarksmentioning
confidence: 94%
“…The effect of SGV division on the outcomes of laparoscopic fundoplication have been evaluated in five prospective randomized studies 2,6-9 and their meta-analysis [11][12][13][14] . These studies showed a longer operative time and intraoperative bleeding 2,6,8,9,11-14 , higher incidence of transient dysphagia 2 and gas-bloating syndrome 7 when SGV are divided.…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 99%